Faktor-Faktor yang Mempengaruhi Pendapatan UMKM Kuliner Online (Studi Empiris pada UMKM Kuliner Online yang Terdaftar di I-jus Melon Kota Semarang Tahun 2018) - Andrajati Muhammad Salim; Arif Muhammad Pujiyono (Universitas Diponegoro, 2021)
In the current era of globalization, it requires business people to think more creatively and innovatively. Support from the government so that business actors can be more competitive in the market competition is needed. Income is one important factor that determines the sustainability of a business. Semarang City is a city that has the potential for various types of businesses, one of which is culinary. In 2018 the number of MSMEs in the city of Semarang experienced an overall reduction. Therefore, this study aims to determine the factors that affect the income of culinary MSMEs in the city of Semarang.This study was analyzed using multiple linear regression (OLS). The population in this study were online culinary MSME players registered at I JUS MELON Semarang. The method used in sampling is purposive sampling. The research sample was obtained by giving a questionnaire to 67 MSME actors. Then used secondary data as supporting data in this study.The results of hypothesis testing show that capital, labor, education, financing have a positive effect on MSME income. Meanwhile, business experience, training, mentoring do no effect on the income of MSMEs. The value of R square in this study was 51.4%. Suggestions for further research are to be able to add other variables that can better explain the research.